An Evaluation of Web Based Instruction In View of the Tutors’ and Students’ Perspectives - (:unkn) unknown (My University, 2008)
0

In today’s world, it is acknowledged by almost all folks of life that the traditional educational institutions are inadequate in educating the growing population. This situation has triggered research into finding ways to provide economical and of high quality education to wider masses of people. Currently, web based instruction seems to be the point that has been reached to meet such a demand. In web based instruction, students’ and tutors’ perspectives play an important role in the facilitation of successful outcomes. Moving on from that, the aim of this research is to investigate web based instruction in view of the tutors’ and students’ perspectives. In order to achieve such an aim, face-to-face interviews were carried out with 10 tutors from the e-MBA Master’s Degree Programme at Bilgi University, and with 10 students registered in the same programme. Nine semi-structured interview questions were used to investigate the participants’ perspectives on web based instruction and the interview data were analyzed accordingly.
Keywords: Eğitim, Eğitim Araştırmaları